Traditional and novel diagnostic biomarkers for acute myocardial infarction - Husam Khalil (SpringerOpen, 2022)
Abstract Background Acute myocardial infarction (AMI) is a leading cause of death worldwide. The first hours of acute myocardial infarction are correlated with the highest risk of death. Therefore, early diagnosis of the infarction seriously affects the efficacy of the treatment administered to the patient. Misdiagnosing patients with chest pain often leads to inappropriate admission of them as acute myocardial infarction patients. The physical examination of the patient, the electrocardiogram, and the assessment of cardiac biomarkers all play an important role in the early diagnosis of acute ischemia, along with the patient's medical history. Main body The present review highlights a number of different biomarkers that are released and elevated in blood during an acute myocardial infarction. Conclusions Analysis of cardiac biomarkers has become the first-line diagnostic tool used in the diagnosis of acute myocardial infarction. Novel markers of acute myocardial infarction, when added to routinely used markers, can provide added value not only in the earlier detection of acute myocardial infarction but also in monitoring the clinical progress of the disease, predicting its consequences, evaluating its prognosis, detecting recurrence, and managing its treatment. This leads to a lower mortality rate associated with acute myocardial infarction. cMyC, IMA, S100, and MicroRNAs can serve as markers of early diagnosis of acute myocardial infarction, whereas myeloperoxidase, sCD40L, PAPPA, and TNF-α can be used to monitor the clinical progress of the disease. In addition, H-FABP, GDF-15, F2 isoprostanes, and ST2 can serve as predictors of AMI complications and mortality. Copeptin, ST2, and SIRT can be useful as prognostic markers of acute myocardial infarction.